March 28, 2017

Post a New Question

Posted by on .

Prove that (3cos^2x + 8sinx-8/cos^2x) = (3sinx-5/sinx+1)

  • Trigonometry - ,

    your lack of the proper use of brackets make your equation much too ambiguous.

    Furthermore, the brackets you do use, make no difference to the meaning.
    If they are removed, there is no change in the order of operation, but ....

    on the left side, who is divided by cos^2 x ?
    is it -8/cos^2 x ? or
    (8sinx-8)/cos^2 x or
    (3cos^2x + 8sinx-8)/cos^2 x

    each would give you a different result, the same is just as confusing on the right side.

  • Trigonometry - ,

    (3cos^2x + 8sinx-8)/cos^2x = (3sinx-5)/sinx+1

  • Trigonometry - ,

    LS = (3(1-sin^x) + 8x - 8)/cos^2x
    = (3-3sin^x+8x-8)/cos^2x
    = -(3sin^2x - 8x + 5)/((1-sinx)(1+sinx))
    = -(3sinx-5)(sinx-1)/((1-sinx)(1+sinx))
    = (3sinx-5)(1 - sinx)/((1-sinx)(1+sinx))
    = (3sinx-5)/(1+sinx)
    = RS

Answer This Question

First Name:
School Subject:

Related Questions

More Related Questions

Post a New Question